Long‐term management options for sea urchin injury: a case series. (1st December 2022) - James, Mariel; Bakkour, Waseem; Checkley, Anna; Calonje, Eduardo; Walker, Stephen L.
Abstract: In the UK, sea urchin‐related injuries (SUIs) most commonly present in returning travellers. Delayed complications mainly affect the skin but nerves, tendons, joints and bones may also be involved. The management of chronic reactions may be challenging and a variety of approaches have been described. Surgical measures are often undertaken, particularly when retained spines are suspected. We demonstrate, through three cases presenting in the UK with chronic SUIs, that conservative management, surgery and intralesional corticosteroids may all be associated with satisfactory outcomes. Management options should consider the presence of retained spines, injury site, symptoms and importantly, patient preference. Abstract : Sea urchin injuries can cause chronic inflammation implicating skin and less commonly, deeper structures. Surgical measures are often undertaken, particularly when there is evidence of retained spines, but other options exist. We demonstrate that conservative management, surgery and intralesional corticosteroids may all be associated with satisfactory outcomes.